Hematopoietic stem cell transplant referral patterns for children with sickle cell disease vary among pediatric hematologist/oncologists' practice focus: A Sickle Cell Transplant Advocacy and Research Alliance (STAR) study. Issue 3 (6th January 2021) - Meier, Emily Riehm; Abraham, Allistair A.; Ngwube, Alex; Janson, Isaac A.; Guilcher, Gregory M.T.; Horan, John; Kasow, Kimberly A.
Abstract: Background: Hematopoietic stem cell transplantation (HSCT) provides a curative therapy for children severely affected by sickle cell disease (SCD). Rejection‐free survival after matched sibling donor (MSD) HSCT is very high, but adoption of HSCT as a curative SCD therapy has been slow. In this study, we assess providers' perceptions about MSD HSCT for children with variable SCD severity, and determine the influence of provider characteristics on HSCT referrals. Procedure: After our Institutional Review Board deemed the study exempt, American Society of Pediatric Hematology/Oncology Clinical Forum listserv subscribers and American Society of Hematology members who self‐identified as pediatric hematologists/oncologists (PHO) were emailed a survey. Analysis was performed to describe and evaluate correlations between participant demographics (including practice focus within PHO) and likelihood of HSCT referral for each scenario. Results: Spearman's rank correlation analysis did not reveal any significant relationship between demographic characteristics except practice focus and likelihood to refer to HSCT for any scenarios. Providers focused on SCD and HSCT were more likely to refer a child who had never been admitted to the hospital or had suboptimal adherence to hydroxyurea than general PHOs. A significantly higher proportion of all respondents would refer a child with β‐thalassemia major (87%) than an asymptomatic child with HbSS (47%, P  < .00001) or non‐HbSS variant (23%, P  < .00001). Conclusion: PSCD and HSCT physicians are more likely to refer for MSD HSCT in almost every condition than general PHO practitioners, likely because of increased awareness of long‐term effects of SCD and safety of MSD HSCT for children with SCD.